IMPLEMENTASI AUGMENTED REALITY PADA MUSEUM BATARA GURU KOMPLEKS ISTANA LANGKANAE LUWU - Aishiyah Saputri Laswi; Andryanto A (ILKOM Jurnal Ilmiah, 2018)
Museum Batara Guru is one of tourist attractions in the city of Palopo. the palace environment is rarely open to the public , lack of information, not optimal communication, and lack of promotion about the history of Palopo city led to the lack of tourist visits to this place. In this research, Augmented Reality (AR) as a computer-based tour guide is developed.AR development is done by modeling the object with 3D model with Unity device and marker recognition using Vuforia device. These AR applications also tested include marker and distance testing. Based on this test results obtained where the image object (heirloom) as a marker can work well. Testing based on shooting marker at a distance of 0.5 to 2 meters. Likewise with the angle of the slope, the marker can be recognized quickly if there is no change in angle when shooting, the greater the angle of the slope the more difficult to recognize the marker.